Analisis Pertanggungjawaban Pidana Terhadap Perantara Jual Beli Narkotika Golongan I (Studi Perkara Nomor 1066/PID/B/2012/PN.TK) - Zainab Ompu Jainah (Universitas Bandar Lampung (UBL), 2015)
Narcotics that occurs in the community and is an unlawful act, either offering for sale, selling, purchasing, receiving, became an intermediary in the sale and purchase, exchange or cede Narcotics Group I. The problem in this paper is how the criminal responsibility of the intermediary selling narcotics Category I not plant?,. The method used is a normative juridical approach. The collection of data based on literature studies, data analysis performed by qualitative analysis. Results of the study describes the criminal responsibility of the perpetrators as an intermediary for the sale and purchase of Narcotics Group I Not Plants by imprisonment for 5 (five) years and a fine of Rp 1,000,000,000 (one billion rupiah) with the provision that if the fine is not paid to be replaced by confinement for 3 (three months). Suggestions can be submitted that needs to be disseminated and counseling dangers of drugs starting from elementary school students to the level of Higher Education.